Does body image influence the relationship between body weight and breastfeeding maintenance in new mothers?. Issue 3 (26th May 2017) - Swanson, Vivien; Keely, Alice; Denison, Fiona C.
Abstract : Objectives: Obese women have lower breastfeeding initiation and maintenance rates than healthy weight women. Research generally focuses on biomedical explanations for this. Psychosocial factors including body image and well‐being after childbirth are less well understood as predictors of breastfeeding. In obese and healthy weight women, we investigated changes in body image between 72 hrs post‐delivery and 6–8 weeks post‐natal, studying how women's body image related to breastfeeding initiation and maintenance. We also investigated how psychological distress was related to body image. Design: Longitudinal semi‐structured questionnaire survey. Methods: Body image and psychological distress were assessed within 72 hrs of birth and by postal questionnaire at 6–8 weeks, for 70 obese and 70 healthy weight women initiating exclusive (breastmilk only) breastfeeding or mixed feeding (with formula milk) in hospital. Breastfeeding was re‐assessed at 6–8 weeks. Results: Obese women were less likely to exclusively breastfeed in hospital and maintain breastfeeding to 6–8 weeks. Better body image was related to maintaining breastfeeding and to lower post‐natal psychological distress for all women, but education level was the most significant predictor of maintenance in multivariate regression including body image and weight status. Body image mediated, but did not moderate the relationship between weight and breastfeeding maintenance. Body image was lower overall in obese women, but all women had low body image satisfaction around childbirth, reducing further at 6–8 weeks. Conclusions: Health professionals should consider women's body image when discussing breastfeeding. A focus on breast function over form may support breastfeeding for all women. Statement of contribution What is already known on this subject? Obesity can negatively affect breastfeeding initiation and maintenance, but there is little information about how psychosocial factors affect this relationship. Body image may be an important factor, but has not been studied in relation to breastfeeding maintenance. What does this study add This article examines the influence of body image on obese and healthy‐weight women's breastfeeding maintenance at 6–8 weeks. Different aspects of body image mediated but did not moderate the relationship between weight status and breastfeeding maintenance, but in multivariate regression, maternal education level was the most significant predictor. Obese women had poorer body image and were less likely to maintain breastfeeding; however, for all women, body image became more negative in this postpartum period. Interventions should normalize positive aspects of women's postnatal bodies, including function rather than form. Addressing body concerns could encourage new mothers to maintain breastfeeding, irrespective of weight status.